2004
DOI: 10.1038/sj.sc.3101671
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic infarction of the spinal cord: involvement of the gray matter plus the border-zone between the central and peripheral arteries

Abstract: Objective: Hemodynamic infarction of the spinal cord that affected an 81-year-old female having a dissecting aortic aneurysm is presented. During the graft replacement operation, systemic hypotension occurred and the patient was subsequently complicated with paraplegia of the lower limbs. The patient died 2 weeks after the surgery due to gastrointestinal bleeding. An autopsy, which did not include the brain, was performed and the spinal cord was sampled. The aim of this report is to describe the pathologic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In addition, the higher metabolic needs of the gray matter also participate in its increased sensitivity to ischemia. Watershed injury of the gray matter ranges from focal anterior or posterior horns lesions, resulting in a typical ‘owl-eye’ or ‘snake-eye’ appearance,6 to complete infarction of the gray substance, with or without white matter involvement 4 5 27…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the higher metabolic needs of the gray matter also participate in its increased sensitivity to ischemia. Watershed injury of the gray matter ranges from focal anterior or posterior horns lesions, resulting in a typical ‘owl-eye’ or ‘snake-eye’ appearance,6 to complete infarction of the gray substance, with or without white matter involvement 4 5 27…”
Section: Discussionmentioning
confidence: 99%
“…Antineuronal nuclear antigen 1 (ANNA-1, also known as anti-Hu), antineuronal nuclear antigen 2 (ANNA-2), antineuronal antigen 3 (ANNA-3), antiamphiphysin, and anticollapsing response mediator protein 5 (CRMP-5) are among the most common antibodies identified in patients with paraneoplastic myelopathies [17]. However, antibodies directed against a number of other surface and intracellular antigens have also been reported [8, 18]. Paraneoplastic myelopathies have been reported in association with many forms of cancer, the most common being breast and lung cancer [17].…”
Section: Clinical Discussionmentioning
confidence: 99%
“…The histopathologic sequelae of ischemia are variable and depend on both the level and extent of vascular compromise. Autopsy findings in patients affected by spinal cord infarction often include preferential involvement of gray matter; however, in a large series, the most severe cases also showed white matter necrosis [18, 20]. Other reports describe involvement of both gray and white matter [21].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to pial versus sulcal artery involvement, Ishizawa et al . [16], in a histopathological study of hemodynamic spinal cord infarction, showed that the infarction involved the gray matter supplied by the central artery while the periphery of the spinal cord supplied by the pial arteries remained intact. In our patient, the pathological finding was altered by the pre-existing cervical spondylotic myelopathy, and delineation between pial versus sulcal vascular territories was not possible.…”
Section: Discussionmentioning
confidence: 99%